A four-decade bibliometric analysis of social entrepreneurship - Sabri, Khairun Najihah; Mohamad, Siti Fatimah; Ungku Zainal Abidin, Ungku Fatimah; Ghazali, Hazrina; Ali@Hamid, Mass Hareeza (Human Resources Management Academic Research Society (HRMARS), 2024)
This paper presents a bibliometric analysis of the previous studies on social entrepreneurship and maps the studies according to publication year and growth, source, language, subject area, countries and institution’s productivity, and also citation metrics. Suggestions for future research based on the four decades of bibliometric analysis are presented towards the end of this paper. The bibliometric analysis was conducted on 1,835 social entrepreneurship articles retrieved from the Scopus database. The articles were published from 1978 until 2021. The software used in the analysis comprised Microsoft Excel for frequency analysis, VOSviewer for data visualization, and Harzing’s Publish or Perish for citation metrics and analysis. The findings show that there has been a tremendous growth of publications on social entrepreneurship over the years, indicating that social entrepreneurship is an emerging research discipline with many potential academic fields to be explored. The subject areas of business, management and accounting are the prominent areas for the social entrepreneurship publication within the context of the Scopus database. This study presents a bird's-eye view of the current trend of social entrepreneurship research globally. The bibliometric analysis indicators from this study serve as a guide to researchers in identifying the most suitable journals for publication, potential collaborators and areas for future research.